Pengaruh Kepuasan dan Kepercayaan terhadap Loyalitas Penumpang Maskapai Garuda Indonesia di Bandar Udara Adi Soemarmo - Arif Fakhrudin (Universitas Proklamasi 45 Yogyakarta, 2020)
Increasing customer loyalty has become a popular topic for managers, consultants, and academics. Optimal service quality is expected to meet customer expectations, so that conditions will create customer satisfaction and loyalty. This study aims to determine the effect of satisfaction and trust on Garuda Indonesia airline passengers’ loyalty at Adi Soemarmo Airport, Boyolali. The type of this research is quantitative research. The data used in this study are primary data obtained through distributing questionnaires to Garuda Indonesia airline passengers at Adi Soemarmo Airport, Boyolali. Of the 100 questionnaires distributed to respondents, 68% response rate can be achieved. Analysis of the data used in this study is multiple linear regression analysis using SPSS version 20 as a data processing aid. The results showed that passenger satisfaction and trust significantly influenced the passengers’ loyalty of Garuda Indonesia airline.